Cordycepin- melittin nanoconjugate intensifies wound healing efficacy in diabetic rats - Rasheed A. Shaik; Mohammed F. Alotaibi; Mohammed Z. Nasrullah; Mohammad W. Alrabia; Hani Z. Asfour; Ashraf B. Abdel-Naim (Elsevier, 2023)
The current study was designed to develop a nanoconjugate of cordycepin-melittin (COR-MEL) and assess its healing property in wounded diabetic rats. The prepared nanoconjugate has a particle size of 253.5 ± 17.4 nm with a polydispersity index (PDI) of 0.35 ± 0.04 and zeta potential of 17.2 ± 0.3 mV. To establish the wound healing property of the COR-MEL nanoconjugate, animal studies were pursued, where the animals with diabetes were exposed to excision and treated with COR hydrogel, MEL hydrogel, or COR-MEL nanoconjugate topically. The study demonstrated an accelerated wound contraction in COR-MEL nanoconjugate -treated diabetic rats, which was further validated by histological analysis. The nanoconjugate further exhibited antioxidant activities by inhibiting the accumulation of malondialdehyde (MDA) and exhaustion of superoxide dismutase (SOD) and glutathione peroxidase (GPx) enzymatic activities. The nanoconjugate further demonstrated an enhanced anti-inflammatory activity by retarding the expression of interleukin (IL)-6 and tumor necrosis factor (TNF)-α. Additionally, the nanoconjugate exhibits a strong expression of transforming growth factor (TGF)-β1, vascular endothelial growth factor (VEGF)-A, and platelet-derived growth factor (PDGFR)-β, indicating enrichment of proliferation. Likewise, nanoconjugate increased the concentration of hydroxyproline as well as the mRNA expression of collagen, type I, alpha 1 (Col 1A1). Thus, it is concluded that the nanoconjugate possesses a potent wound-healing activity in diabetic rats via antioxidant, anti-inflammatory, and pro-angiogenetic mechanisms.